ASEAN Digital Economy Framework Agreement (DEFA): Implications for Digital Trade and Regional Economic Integration - Lee, Brice Tseen Fu; Dinh, Linh Dieu; Sims, Juan Pablo; Bettani, Salman Ali (UI Scholars Hub, 2025)
The ASEAN Digital Economy Framework Agreement (DEFA) represents a pivotal initiative in advancing regional digital integration and economic development. This paper explores DEFA's potential impacts on digital trade and regional economic cohesion within ASEAN. By reviewing ASEAN’s official publications and relevant literature, the study evaluates how DEFA aims to address the challenges posed by fragmented digital regulations and infrastructure. The framework's emphasis on harmonizing digital standards and enhancing interoperability is anticipated to facilitate smoother cross-border transactions and reduce regulatory barriers, thereby driving trade and investment in digital services. Economic projections suggest that DEFA could significantly enhance ASEAN’s digital economy, potentially increasing its value from US300 billion to up to US2 trillion by 2030. The framework’s focus on addressing current digital trade barriers and fostering innovation positions it as a transformative tool for regional integration. The findings underscore DEFA’s potential to unify digital markets and stimulate economic growth, highlighting its importance for ASEAN's future digital landscape.